MENINGKATKAN HASIL BELAJAR KONSEP HIDROLISIS GARAM MELALUI MODEL COOPERATIVE LEARNING TIPE TGT PADA SISWA KELAS XI-B1 MAN MODEL GORONTALO - Heni, Wa; Pikoli, Masrid; Suleman, Nita (Jurnal Entropi, 2009)
This research is one of class art (PTK). This research conducted by because referring low the activity and student\'s motivation in learning the material salt hydrolysis which fetch, to student\'s result. One of solution which can be do by the teacher is applying the cooperative learning type TGT (Teams Games Tournament). The sample of this research at student\'s class XI-B1 MAN Model Gorontalo academic years 2008/2009 which consists twenty student\'s. This research could be do consists of the sicluss. With some changed to low which be found in every sicluss. The first sicluss is applying cooperative learning type TGT (Teams Games Tournament), then second sicluss is art of part the first sicluss based on result of observation and result of evaluation. The result of analysis at the first sicluss indicated the student\'s who get score 6,5 or more consists 16 student\'s (80%) and the student\'s which get score under 6,5 consists of 4 student\'s (20%) with classical capability 87,18% at the first sicluss the result of student\'s not be categorized criterion of result which conducted by observer is 85%, so could be continuo to second sicluss. When at the second sicluss, the student\'s who get score 6,5 or more consists 20 student\'s (100%). This is indicated if applying cooperative learning type TGT (Teams Games Tournament) at the material salt hydrolysis can could be improving result of class XI-B1 MAN Model Gorontalo.